Concerts and other activities of Tuvan musicians in the 1990s mediated by Bernard Kleikamp via his companies Paradox Concert Agency and Pan Records - Kleikamp, Bernard (The New Research of Tuva, 2024)
The article is based on a chronological review of the author's work with musicians from Tuva during the 1990s. He is a producer and ethnomusicologist. From 1978 to 2003, he organized concerts through Paradox Concerts, during which more than 500 concert tours were held, resulting in a total of over 5,000 performances.During this period, the author brought Tuvan music to listeners in 13 different countries on five continents, hosting over 200 events including concerts, festivals, workshops, educational programs, live radio broadcasts, television appearances, CD productions, modern operas (Noach), ballets (Aurora), and joint multimedia projects with artists from various cultures (Vox, Voices of God, Globe Orchestra). Additionally, interviews, university research programs, and studio recordings were conducted for CDs and radio.
Keywords: Tuvan music; Tuvan musician; Tuvan band; tour; concert; throat singing; Tuvan throat singing